2010
DOI: 10.1158/1940-6207.capr-09-0163
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor Expression and Gene Copy Number in the Risk of Oral Cancer

Abstract: Leukoplakia is the most common premalignant lesion of the oral cavity. Epidermal growth factor receptor (EGFR) abnormalities are associated with oral tumorigenesis and progression. We hypothesized that EGFR expression and gene copy number changes are predictors of the risk of an oral premalignant lesion (OPL) progressing to oral squamous cell carcinoma (OSCC). A formalin-fixed, paraffin-embedded OPL biopsy specimen was collected from each of 162 patients in a randomized controlled clinical trial. We assessed E… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
97
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 111 publications
(100 citation statements)
references
References 45 publications
2
97
1
Order By: Relevance
“…In OPML patients enrolled in a retinoid/beta-carotene chemoprevention trial, EGFR protein overexpression and gene copy number gain was associated with increased risk of development of OSCC [33]. Likewise, Poh et al observed that EGFR gene copy number gain occurred more frequently in lesions that subsequently progressed to cancer versus not [35].…”
Section: Prognostic Markers Beyond Lohmentioning
confidence: 99%
See 1 more Smart Citation
“…In OPML patients enrolled in a retinoid/beta-carotene chemoprevention trial, EGFR protein overexpression and gene copy number gain was associated with increased risk of development of OSCC [33]. Likewise, Poh et al observed that EGFR gene copy number gain occurred more frequently in lesions that subsequently progressed to cancer versus not [35].…”
Section: Prognostic Markers Beyond Lohmentioning
confidence: 99%
“…These include (but are not limited to) podoplainin [26], deltaNp63 [17], cyclin D1 genotypes [27], specific mRNA expression [28] and DNA methylation [29] profiles, miRNA-31 [30], human telomerase RNA component (hTERC) gene copy number [31], ABCG2 and BMI-1 expression [32], and EGFR protein, mRNA expression and gene copy number gains [33]. Most of these studies, however, consisted of retrospective analyses, including varying (but often limited) number of specimens, without validation on i ndependent datasets.…”
Section: Prognostic Markers Beyond Lohmentioning
confidence: 99%
“…Increased or aberrant expression of the EGFR or its ligands may lead to many processes important for tumor growth, including cell proliferation, survival, angiogenesis, invasion, and metastasis (Janmaat & Giaccone, 2003). A pervious study investigating EGFR gene in oral premalignant lesion specimens found that increased EGFR gene copy number was associated with higher risk of oral cancer (Taoudi Benchekroun et al, 2010). Other studies found significant increases in EGFR copy number and EGFR immuno-reactivity in oral squamous cell carcinoma patients when compared with long-term betel quid chewers, or compared with matched adjacent oral mucosa (Chiang et al, 2008).…”
Section: Epidermal Growth Factor Receptormentioning
confidence: 99%
“…Some biomarkers of risk of malignant transformation, such as loss of heterozygosity (LOH), 68 and epithelial growth factor receptor ( EGFR ) gene copy number gain, 9 have been identified and validated in OPL. Retrospective and prospective studies completed initially by our group 6 and subsequently by others 7,8 demonstrate that LOH profiles (primarily at 3p14 and/or 9p21) in OPL are the most robust marker of cancer risk in this setting.…”
Section: Introductionmentioning
confidence: 99%